2015
DOI: 10.1002/jaba.213
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of massed and distributed practice on skill acquisition for children with autism

Abstract: We replicated and extended the findings of Haq and Kodak (2015) by evaluating the efficiency of massed and distributed practice for teaching tacts and textual and intraverbal behavior to 3 children with autism. Massed practice included all practice opportunities conducted on 1 day during each week, and distributed practice included practice opportunities conducted across several days during the week. The results indicated that distributed practice was more efficient for all participants. Suggested areas for fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Similarly, previous research on massed and distributed practice (Haq & Kodak, ; Haq et al, ) compared the effects of grouping many practice opportunities into one session (referred to as massed practice) versus spacing practice opportunities across days (referred to as distributed practice). The results of those studies showed participants required fewer trials‐ and minutes‐to‐mastery during distributed practice opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, previous research on massed and distributed practice (Haq & Kodak, ; Haq et al, ) compared the effects of grouping many practice opportunities into one session (referred to as massed practice) versus spacing practice opportunities across days (referred to as distributed practice). The results of those studies showed participants required fewer trials‐ and minutes‐to‐mastery during distributed practice opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, other studies arranged larger stimulus set sizes. For example, Haq et al () taught tacts and textual responses with sets of 10 stimuli to two participants who received special education services in their local school district. Similarly, Yaw et al () conducted training with sets of 15 stimuli for students with ASD or specific learning disabilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The trial‐initiation response could be considered an observing response in that it increases the likelihood that the participant will make sensory contact with the first stimulus presented. It should be noted, however, that it is fairly common practice not to require an observing response or differential observing response in applied studies that target auditory–visual conditional discriminations for participants with autism spectrum disorder (e.g., Carey & Bourret, ; Carp et al, ; Delfs et al, ; Dittlinger & Lerman, ; Fisher et al, ; Haq et al, ; McGhan & Lerman, ; Paden & Kodak, ). Moreover, recent applied research did not demonstrate consistently superior auditory–visual conditional discrimination acquisition in a condition that required a differential observing response relative to a condition that did not (Vedora, Barry, & Ward‐Horner, ).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies evaluated the effects of antecedent (e.g., repeating vs. not repeating the discriminative stimulus at each prompting step; Humphreys, Polick, Howk, Thaxton, & Ivancic, 2013) or consequence (e.g., token reinforcement vs. natural contingencies; Mason, Davis, & Andrews, 2015) manipulations during intraverbal training, as well as the outcomes of different instructional formats in the acquisition of intraverbal responses (e.g., blocked trials; Haggar, Ingvarsson, & Braun, 2017). Haq et al (2015) compared intraverbal acquisition of massed and distributed trials in three children with ASD. During massed trials, the experimenter conducted all training opportunities 1 day during each week; during distributed trials, the experimenter conducted all training opportunities across several days during the week.…”
Section: Intraverbalsmentioning
confidence: 99%